Scope and approaches of integrating sustainability issues in public procurement process for sustainable development of Bangladesh - Rahman, Md Saifur; Islam, Md Zohurul (© 2017 Inderscience Enterprises Ltd., 2018)
This article was published in the International Journal of Procurement Management [© 2017 Inderscience Enterprises Ltd.] and the definite version is available at: https://doi.org/10.1504/IJPM.2017.082785 The Article's website is at: http://www.inderscience.com/offer.php?id=82785